MEKANISME MEMBAWA LARI PEREMPUAN YANG DILAKUKAN SECARA HUKUM ADAT NIAS (Studi di Desa Hilifalago) - Lidwina Gaurifa (Jurnal Panah Hukum, 2023)
Customary law is an unwritten law, but its existence is a law that lives, grows, and develops in people's lives and as a law that applies, is obeyed, and respected by the community. Carrying women away is a form of marriage that violates applicable customary law, because marriage can be considered valid if it is in accordance with religious law, customary law, community views and the law governing marriage. One form of marriage that violates customary law is taking women away which occurred in Hilifalago Village. In that case, the perpetrator was subject to customary sanctions, namely one pig, three million rupiah in cash, and was excommunicated from the family. The type of research used is sociological legal research with an exploratory approach. Data was collected using primary data obtained from observations or observations, interviews, and document studies. The data analysis used is the case study method (observational case studies) with a quantitative approach that combines qualitative and quantitative data input at the same time using deductive thinking methods. Based on the findings of the research and discussion, it can be concluded that the settlement mechanism for carrying away women carried out according to Nias customary law (Study in Hilifalago Village) is traditional leaders (Siulu), community leaders (Si'ila), and village heads of both parties negotiating In solving the problems that occur then customary law sanctions are imposed on the perpetrators of elopement so that there is no commotion because their actions are contrary to customary law. So referring to this, every community who violates the provisions of customary law, especially carrying away women, will be subject to customary sanctions, namely one pig of 87 kg (6 Alisi), a minimum of three million rupiah and some are excommunicated from families where their families cannot accept it. they. The author suggests that customary law be used as a guide in deciding everything, especially in marriage so that they always follow the existing customary law rules